Relasi Gender terhadap Tokoh Perempuan dalam Cerpen Jemari Kiri Karya Djenar Maesa Ayu dan Sepasang Mata Dinaya yang Terpenjara Karya Ni Komang Ariani - Anggraini, Rika; R, Syahrul (AHKAM, 2025)
This research aims to describe gender relations towards female characters in short stories Jemani Kini by Djenar Maesa Ayu and Sepasang Mata Dinaya yang Terpenjara by Ni Komang Ariani. This research was conducted by applying descriptive qualitative method. The object of this research is short story Sepasang Mata Dinaya yang Terpenjara Karya Ni Komang Ariani and short story Jemari Kini Karya Djenar Maaesa Ayu. Data collection was done by reading and listening to both short stories. This research focuses on gender relations towards female characters. The results of this study found the existence of gender relations towards female characters in these two short stories, namely women are still placed in the position of housewives, women who try to overcome the thoughts that exist in the society. In this short story there is also a woman's lack of freedom after she gets married. Basically, women can get their rights in social interaction. There are still thoughts that influence traditions and ways of thinking that say that women are better off carrying out their obligations in household affairs.